Até que a morte nos separe : estudo de casos de homicídios contra mulheres e a aplicação da Lei Maria da Penha (Comarca de Toledo/PR, 2009-2013) - Nodari, Maísa Kelly (2016)
On August 7th, 2006 it was enacted the Law n.º 11,340/06, popular known as Maria da Penha Law, which essentially aims to restrain and prevent any forms of violence against women based on gender issues. Starting from this premise, the paper, through qualitative research in documentary sources, analyzes the speech emanated from the various legal actors in four criminal cases already judged by the Jury Trial of Toledo District. These processes were processed duo to homicides committed by men against women with whom they maintained close relationship of affection, and are problematized in the context of domestic violence and gender violence, this one understood from power relations. It is analyzed, withal, the legal treatment given to this case, since the beginning of the investigations until its conclusion, focusing on the emphases and the silences noticed to the construction of a legal truth and the Maria da Penha Law application.